Trends and Challenges in Environmental Education for Young Children: A Systematic Literature Review - Mutiarasari, Airin; Syaodih, Ernawulan; Djoehaeni, Heny (FKIP Universitas Lampung, 2025)
Trends and Challenges in Environmental Education for Young Children: A Systematic Literature Review. Objectives: This study aims to systematically review and synthesize research on environmental education for young children with a focus on identifying global trends, pedagogical approaches, implementation challenges, and future directions. The objective is to provide a comprehensive overview that informs future research and practice promoting sustainability education for young children. Methods: A systematic literature review was conducted using international databases (Scopus) to collect and analyze peer-reviewed articles published over the past decade. Inclusion criteria covered studies focusing on environmental education in early childhood, addressing both pedagogical practices and conceptual frameworks. The selected articles were analyzed thematically to identify prevailing trends, strategies, barriers, and recommendations. Findings: The analysis reveals a growing interest in early childhood environmental education, marked by a significant increase in publications after 2020. The study is dominated by the participation of developed countries rather than developing countries. Four main pedagogical approaches have been set: experiential-based learning, garden-based learning, storytelling with an ecological project theme, as well as project-based learning. Regardless of the profit, several challenges persist, including limited access to the green room, inadequate educator training, and an inconsistent framework for measuring ecoliteracy. This finding also highlights the scarcity of longitudinal studies, which limits our understanding of short-term effects. Conclusion: Early childhood environmental education plays a crucial role in promoting ecoliteracy, social-emotional development, and pro-environmental attitudes. However, this sector still confronts a conceptual gap, methodological, as well as significant geographic. Tightening the educator training, integrating sustainability in the curriculum, and carrying out more fundamental, inclusive, long-term studies to work on environmental education in early childhood effectiveness. Keywords: environmental education, sustainability, young children.